Analisis Faktor Kesulitan Belajar Pada Pembelajaran Matematika Ditinjau Melalui Kemampuan Koneksi Matematika - Rachmataha, Vina (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2020)
This study aims to analyze the factors of mathematics learning difficulties in terms of mathematical connection skills in Banyuwangi, Bandongan, Magelang Elementary Schools. This research is a kind of descriptive research. The population in this study were all 5th grade elementary school students in the Banyuwangi sub-district. The sample of this study was all 5th grade students of all Banyuwangi villages which numbered 64 students. The sampling technique from the sampling study was saturated because the entire population was used in this study. The method of data collection is done by using diagnostic tests of mathematical connection skills, student interviews, and teacher observation. The research procedure begins with the preparation stage, then the implementation, and analysis / reflection. The results showed that the factors of mathematics learning difficulties in terms of the mathematical connection ability of elementary school students in Banyuwangi Subdistrict, the average value of the overall percentage showed a figure of 57.8% as the highest number, which is located in the low category. The percentage of categories is very low at 20.6%, moderate category 12.8%, and high category 8.9%. These results are supported by the results of student interviews and documentation of values that are in line with the results of the test. So, the ability to connect mathematics in elementary schools throughout the Banyuwangi Village is included in the low category. 93.6% of students find it difficult to find relationships from representations of systematic concepts and procedures. 59.3% of students have difficulty understanding the relationships between mathematical topics. 43.8% of students have not been able to use mathematics in solving problems in everyday life. 53.1% of students find it difficult to understand equivalent concept representations. 42.2% of students find it difficult to find a relationship between procedures with one another that is equal. 54.7% of students have difficulty using the connection between mathematics and mathematics itself and with other sciences.